THE EFFECT OF PREDICTION STRATEGY TO THE STUDENTS’ READING ABILITY AT TENTH GRADE OF SMA NEGERI 2 SIBORONGBORONG - Sando Simanjuntak; Novita N Hutabarat; Lamhot M. Situmeang; Musrafidin Simanullang; Lamma Sihotang (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2021)
This study deals with the effect of prediction strategy to the students’ reading ability.The objectives of this study is to find out where the prediction strategy significantly effective to the student’ reading ability especially in descriptive text.the population of this study were tenth grade of smanegeri 2 siborongborong in academic year 2018/2019 which consist of 350 students .the sample of tis study were 34 students which devided into two groups that is control group and Experimental group.where incontrol group there were 17 students taught without using prediction strategy and in experimrntal group there is 17 students taught with prediction strategy.the instrument for collecting the data was used descriptive text which consist of 20 numbers and each number has five option there were a,b,c,d,ore.after collecting the data the score of pre test and post test from control group and experimental group were different.where there was a significant improvement between both of groups.Where before applying the prediction strategy the mean of the students’ score are 50 but after applying prediction strategy the mean of the students’ score are 80 from the score above there was a significant effect of prediction strategy to the students’ reading ability .